Analysis of the Application of Disciplinary Penalties Against Police Members Who Perform Siri Marriage in the Legal Area of Rokan Hilir Police Station - Pratama Sitepu, Edi; Risdalina, Risdalina; Kumalasari Munthe, Indra (International Journal Labs, 2024)
This research aims to find out about the Analysis of the Application of Disciplinary Penalties Against Police Members Who Perform Siri Marriage in the Rokan Hilir Police District. This research uses Normative-empirical legal methods, namely through a qualitative approach. The data in this study uses secondary data (literature review). The discussion results in the application of disciplinary penalties against members of the Indonesian National Police who commit Siri marriage in the Rokan Hilir Police Legal Area by Government Regulation (PP) No. 2 of 2003 concerning Disciplinary Regulations for Members of the Indonesian National Police. By Article 1 number 5, disciplinary actions that are constructive are imposed directly on members of the Indonesian National Police.